OPTIMALISASI APLIKASI MENDELEY SEBAGAI SARANA PENELITIAN DI SEKOLAH TINGGI TEOLOGI TABGHA BATAM - Feri Aman Mendrofa; George Rudi Hartono Pasaribu (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Skills in using technology facilities and applications are indispensable in the preparation of research journals and dedication to lecturers at the Tabgha Theological Seminary of Batam, especially for journal publications that meet publication standards. The use of the right application is an effort made to meet the above standards, therefore Tabgha Theological Seminary Batam uses the tools available in the Mendeley application. In this service, the method applied is by holding Mendeley application training which contains an introduction to the Mendeley application and its benefits, installation steps on lecturer computers, installation on Microsoft Word, application of citations and bibliography. The result of this training is that lecturers can optimally use the Mendeley application so that they can present journal publications that meet predetermined standards and templates. The results of the Community Service questionnaire initially found that only 25% had Mendeley installed; 12.5% ​​already have a Mendeley account and 12.5% ​​are able to use Mendeley in various research reports, and after training 100% of the lecturers have installed, have an account and are able to use the Mendeley Application proficiently.